Species composition of pests of grain stocks in storage of grain - Serednyak, D.P.; Fedorenko, V.P. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2016)
Analyzed the phytosanitary condition of warehouses and silos for storage of grain and grain products. The species composition of the most common pests of grain stocks in different granaries. The results of studies, identified the dominant species.